The corrosion behaviour of candidate container materials for the disposal of high-level waste and spent fuel – a summary of the state of the art and opportunities for synergies in future R&D. (28th April 2017) - Padovani, C.; King, F.; Lilja, C.; Féron, D.; Necib, S.; Crusset, D.; Deydier, V.; Diomidis, N.; Gaggiano, R.; Ahn, T.; Keech, P. G.; Macdonald, D. D.; et al.
ABSTRACT: This paper presents a state-of-the-art analysis of the expected degradation processes of a variety of candidate container materials for the disposal of high-level waste and/or spent nuclear fuel. The work, focusing on the most recent developments, has been performed under the auspices of the Implementing Geological Disposal Technology Platform in the context of an international conference hosted by the Nuclear Waste Management Organisation of Canada (NWMO). The scope of the analysis includes the expected corrosion and environmentally assisted cracking behaviour of copper, carbon steel and titanium in contact with relevant buffer materials (e.g. bentonite, cement) and in conditions expected in an underground disposal facility (long-term anoxic conditions). Considerations relative to the expected evolution of the environmental conditions (especially in the period following backfilling) are also presented. Beyond summarising the current state of knowledge, areas in which opportunities for international collaboration may be present are also highlighted. This paper is part of a supplement on the 6th International Workshop on Long-Term Prediction of Corrosion Damage in Nuclear Waste Systems.